2009
DOI: 10.1038/emboj.2009.317
|View full text |Cite
|
Sign up to set email alerts
|

CYLD negatively regulates cell-cycle progression by inactivating HDAC6 and increasing the levels of acetylated tubulin

Abstract: CYLD is a tumour-suppressor gene that is mutated in a benign skin tumour syndrome called cylindromatosis. The CYLD gene product is a deubiquitinating enzyme that was shown to regulate cell proliferation, cell survival and inflammatory responses, mainly through inhibiting NF-jB signalling. Here we show that CYLD controls cell growth and division at the G 1 /S-phase as well as cytokinesis by associating with a-tubulin and microtubules through its CAP-Gly domains. Translocation of activated CYLD to the perinuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
143
3
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 49 publications
7
143
3
7
Order By: Relevance
“…We have shown in previous studies that CYLD reduces proliferation and cyclin D1 expression by slowing the G1/S phase transition in keratinocytes and melanoma cells (Wickstrom et al, 2010). To investigate whether the cells with reduced CYLD expression were proliferating, we used the proliferation marker Ki-67 and cyclin D1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown in previous studies that CYLD reduces proliferation and cyclin D1 expression by slowing the G1/S phase transition in keratinocytes and melanoma cells (Wickstrom et al, 2010). To investigate whether the cells with reduced CYLD expression were proliferating, we used the proliferation marker Ki-67 and cyclin D1.…”
Section: Resultsmentioning
confidence: 99%
“…Hh/GLI signaling has been shown to induce proliferation via activation of critical G1/S cell cycle genes, including D-type cyclins (Kenney and Rowitch, 2000;Regl et al, 2004). We recently demonstrated that CYLD reduces cell proliferation by decreasing the rate of cell division at the G1/S phase (Wickstrom et al, 2010). Here, we found that release of synchronized keratinocytes by addition of tetracycline caused a delay in G1 to S phase transition in CYLD-transfected cells, but not in mock-transfected cells (Figure 4d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative splicing [161] 14-3-3z Lys 49 /Lys 120 Suppression of growth and survival signalling [162] (GRK2) [35,36], aurora A [37] and protein kinase C isoform z (PKCz) [38], are also found to phosphorylate and increase HDAC6 tubulin deacetylase activity at positions that remain undefined. Another example of enhanced HDAC6 activity by phosphorylation is provided by protein kinase CK2 (formerly casein kinase II), which phosphorylates HDAC6 at position 458 (Ser 458 ) to enhance the formation and clearance of aggresomes [39].…”
Section: Sam68mentioning
confidence: 99%
“…Phosphorylation of TPPP1 by Rho-associated coiled-coil kinase (ROCK) and cyclin-dependent kinase 1 (CDK1) impairs the interaction between TPPP1 and HDAC6, which, in turn, results in increased HDAC6 activity followed by a decrease in cell motility and an increase in cell proliferation, respectively [46,47]. Moreover, a broad spectrum of regulators, which directly interact with and inhibit HDAC6 tubulin deacetylase activity or aggresome formation ability, has been well documented, including paxillin [48], CYLD [49,50], dysferlin [51], Mdp3 [52], p62 [53] and RanBPM [54].…”
Section: Sam68mentioning
confidence: 99%